2020
DOI: 10.3390/app10062018
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Grouting Compactness in Tendon Duct Using Multi-Sensing Electro-Mechanical Impedance Method

Abstract: The structural integrity of post-tensioning prestressed concrete structures with tendon ducts highly depends on the grouting quality in construction. This paper proposes a real-time approach to monitoring the grouting compactness in tendon ducts using the multi-sensing electro-mechanical impedance (EMI) method. When Lead Zirconate Titanate (PZT) transducers with different pre-selected dimensions are serially connected and mounted on a structure at distributed locations, each PZT provides unique resonance frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The use of active sensing approach has been recently extended for detection of longitudinal grouting quality and grouting compactness in prestressed curved tendon ducts, it has been found that voltage signals, power spectral density (PSD) energy and wavelet packet energy amplitudes increases as the grouting level increases with significant increase at 100% grouting level in prestressed curved tendon ducts [15,16]. The experimental and numerical analysis of grouting compactness in tendon duct has been carried by using multi-sensing EMI approach and their quantification was done by mean absolute percentage deviation (MAPD) [17]. Many researchers used the EMI approach for damage monitoring in RC beams under different loading conditions using different piezo sensor configurations such as monitoring of flexural damage states using embedded PZT sensor, flexural/shear monotonic and cyclic loading damage using surface-bonded/embedded PZT patch, damage in shear RC beams using embedded and bonded PZT sensor, damage in RC structural members under cyclic loading using surface-bonded, embedded or externally bonded PZTs patch via portable monitoring system, impact damages in RC beam using embedded PZT sensors and crack evaluation under pseudo-dynamic loading in RC column using embedded PZT sensor [18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The use of active sensing approach has been recently extended for detection of longitudinal grouting quality and grouting compactness in prestressed curved tendon ducts, it has been found that voltage signals, power spectral density (PSD) energy and wavelet packet energy amplitudes increases as the grouting level increases with significant increase at 100% grouting level in prestressed curved tendon ducts [15,16]. The experimental and numerical analysis of grouting compactness in tendon duct has been carried by using multi-sensing EMI approach and their quantification was done by mean absolute percentage deviation (MAPD) [17]. Many researchers used the EMI approach for damage monitoring in RC beams under different loading conditions using different piezo sensor configurations such as monitoring of flexural damage states using embedded PZT sensor, flexural/shear monotonic and cyclic loading damage using surface-bonded/embedded PZT patch, damage in shear RC beams using embedded and bonded PZT sensor, damage in RC structural members under cyclic loading using surface-bonded, embedded or externally bonded PZTs patch via portable monitoring system, impact damages in RC beam using embedded PZT sensors and crack evaluation under pseudo-dynamic loading in RC column using embedded PZT sensor [18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Structural health monitoring (SHM) [8,9] is playing an increasingly important role in the safety and reliability of infrastructures by providing real-time early warnings of structural abnormities [10,11] based on the integrated sensors [12,13] and advanced algorithms [14]. As one of the many transducers employed in the field of SHM, piezoelectric transducers possess the advantages of low cost, quick response [15,16], wide bandwidth [17], sensing and actuation [18,19], energy harvesting [20,21], enabling many applications from passive applications, such as vibration sensing [22] and acoustic emission detection [23], to active applications, such as SHM based on active sensing [24,25] and electromechanical impedance [26][27][28]. Since the introduction of the piezoceramic-based smart aggregate (SA) [29][30][31] that provides an effective way to protect the fragile piezoceramic patch, piezoceramic transducers have been employed extensively in concrete structures.…”
Section: Introductionmentioning
confidence: 99%
“…In SHM of civil infrastructure, notable research based on advanced algorithms, such as damage index-based damage assessment [ 8 , 9 ], image-based damage locating [ 10 ] and artificial intelligence algorithms [ 11 ], have been reported to provide solutions to real-time monitoring and early warning of civil infrastructure [ 12 , 13 ] by using various sensors, such as strain gauges [ 14 , 15 ], piezoelectric transduces [ 16 , 17 ], optical fiber sensors [ 18 , 19 ], etc. With advantages of low cost, wide bandwidth [ 20 ] and quick time response [ 21 , 22 ], apart from in SHM of civil infrastructure, piezoelectric transducers have also been widely used in other fields, including aerospace [ 23 , 24 , 25 , 26 ], transportation [ 27 , 28 ] and energy [ 29 , 30 ], and they have displayed good applicability in both passive and active situations [ 31 , 32 ], such as vibration sensing [ 33 ], acoustic emission [ 34 ], active sensing and electromechanical impedance-based damage detection [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%